2019
DOI: 10.1029/2019wr025153
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Reactive Transport Model for Field‐Scale Simulation of Microbially Induced Carbonate Precipitation

Abstract: Microbially induced carbonate precipitation (MICP) is a promising technique that could be used for soil stabilization, for permeability control in porous and fractured media, for sealing leaky hydrocarbon wells, and for immobilizing contaminants. Many further field trials are required before optimum treatment strategies can be established. These field trials will be costly and time consuming to \carry out and are currently a barrier to transitioning MICP from a lab‐scale process to a practical field‐scale depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 55 publications
0
53
0
Order By: Relevance
“…MICP has been proven to reduce permeability and enhance mechanical strength even at large, field-relevant scales (e.g. [33,41,46,56,59]). There are several reviews about the understanding of bio-improved soils (e.g.…”
Section: Biogeochemical Processes In Subsurface Porous Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…MICP has been proven to reduce permeability and enhance mechanical strength even at large, field-relevant scales (e.g. [33,41,46,56,59]). There are several reviews about the understanding of bio-improved soils (e.g.…”
Section: Biogeochemical Processes In Subsurface Porous Mediamentioning
confidence: 99%
“…to mitigate leakages from a geological gas reservoir into above aquifers in advance (e.g. [12,13,35,41,46]). Our limited knowledge about the interaction of the processes that govern biogeochemical systems leads to several modeling approaches that differ, e.g., in their level of detail.…”
Section: Biogeochemical Processes In Subsurface Porous Mediamentioning
confidence: 99%
“…The MICP treatment method has gained interest due to its relatively environmentally friendly characteristics, low energy consumption, and sustainable advantages [ 7 ]. Many recent studies have shown that the MICP treatment technique could effectively improve strength and stiffness [ 8 , 9 , 10 , 11 , 12 ]; decrease permeability [ 13 , 14 , 15 , 16 ]; increase resistance to liquefaction [ 17 , 18 , 19 ]; and enhance concrete self-healing [ 20 , 21 , 22 ]. All the above studies indicated that as a new technology for foundation reinforcement, MICP could effectively improve stiffness, strength, and permeability.…”
Section: Introductionmentioning
confidence: 99%
“…One step towards overcoming this difficulty is the numerical model that we provide for EICP. For MICP, numerical models have been shown to be capable of capturing the complex interplay of hydraulics, precipitation reactions, and the change in hydraulic properties [12,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%